Synthesis of New Azocompounds and Fused Pyrazolo[5, 1‐c][1, 2, 4]triazines Using Heterocyclic Components. (30th May 2013) - Ledenyova, Irina V.; Didenko, Vitaly V.; Shestakov, Alexander S.; Shikhaliev, Khidmet S.
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>